Metabolic traits of an uncultured archaeal lineage -MSBL1- from brine pools of the Red Sea - Mwirichia, Romano K.; Intikhab, Alam; Mamoon, Rashid; Manikandan, Vinu; Wail, Ba-Alawi; Kamau, Anthony A.; Ngugi, David K.; Göker, Markus; Klenk, Hans-Peter; Bajic, Vladimir; Ulrich, Stingl (My University, 2016)
The candidate Division MSBL1 (Mediterranean Sea Brine Lakes 1) comprises a monophyletic group of uncultured archaea found in different hypersaline environments. Previous studies propose methanogenesis as the main metabolism. Here, we describe a metabolic reconstruction of MSBL1 based on 32 single-cell amplified genomes from Brine Pools of the Red Sea (Atlantis II, Discovery, Nereus, Erba and Kebrit). Phylogeny based on rRNA genes as well as conserved single copy genes delineates the group as a putative novel lineage of archaea. Our analysis shows that MSBL1 may ferment glucose via the Embden–Meyerhof–Parnas pathway. However, in the absence of organic carbon, carbon dioxide may be fixed via the ribulose bisphosphate carboxylase, Wood-Ljungdahl pathway or reductive TCA cycle. Therefore, based on the occurrence of genes for glycolysis, absence of the core genes found in genomes of all sequenced methanogens and the phylogenetic position, we hypothesize that the MSBL1 are not methanogens, but probably sugar-fermenting organisms capable of autotrophic growth. Such a mixotrophic lifestyle would confer survival advantage (or possibly provide a unique narrow niche) when glucose and other fermentable sugars are not available.
doi:10.1038/srep19181